Active learning a practical guide for college faculty - Weimer, Maryellen 1947- (Madison, Wisconsin Magna Publications, 2017)
Active Learning: A practical Guide for College Faculty offers everyday guidance for implementing and improving active learning in the college classroom. This collection of articles is appropriate for both the complete novice as well as the instructor who may have used active learning techniques before.
"Some articles in this book have been previously published in 'The Teaching Professor' newsletter, 'Online Classroom' newsletter, 'Faculty Focus,' or have been adapted from Magna Online Seminars or 20-Minute Mentor presentations."--Title page verso.
Includes bibliographical references.
Keywords: Active learning; College teaching -- Methodology; Active learning -- Case studies; College teaching -- Methodology -- Case studies